Continuous‐Flow Solid‐Phase Peptide Synthesis: A Revolutionary Reduction of the Amino Acid Excess. Issue 11 (5th September 2014) - Mándity, István M.; Olasz, Balázs; Ötvös, Sándor B.; Fülöp, Ferenc
Abstract A highly efficient continuous‐flow technique for the synthesis of peptides was developed. The method allows the application of only 1.5 equivalents of amino acids during coupling, while yielding virtually quantitative conversions. A mesoscale reactor was constructed which permits the use of high temperature and pressure during the synthesis. A complete reaction parameter optimization was carried out. Under the optimum conditions, the couplings of all 20 proteinogenic amino acids were achieved with 1.5 amino acid equivalents with quantitative conversions. As a demonstration of the efficiency of the methodology, difficult sequences and β‐peptide foldamers with alicyclic side‐chains were synthetized in excellent yields and with lower costs thanks to the lower amounts of amino acid and solvent used. By this the synthesis is highly economic and sustainable. Importantly, exotic and expensive artificial amino acids were incorporated into peptidic sequences by the utilization of a reasonable number of amino acid equivalents. The synthesis can be performed in quantities of microgram to gram in an automated way.